Development of Maluku Nutmeg (Myristica Fragrans Houtt.): Collaborations, Opportunities and Challenges - Leunufna, Semuel (European Journal of Applied Sciences, 2022)
Nutmeg (Myristica fragrans Houtt.) is one of the few commoditites from Indonesia, especially Maluku islands, which are highly demended in international market for centuries and is the base of an international trading route known as “spice route” where Banda “spice island’, Maluku as the center. This study aimed at elaborating the development of nutmeg commodity in its center of origination and cultivation. Data were acquired during implementation of the Blended Learning-Value Chain project, a joint project between Indonesia and Netherlands, nutmeg innovation platform activities, as well as literature research and assessment. Efforts in nutmeg development in Maluku are implemented in inclusive and sustainable manner through collaboration of different institutions and stake holders along the value chain system of nutmeg commodity. Indentification of opportunities, challenges and problems togather with the way of dealing with them are carried out to be further implemented the findings in the field. Suatainable development is persieved in term of environment and biodiversity, humanity especially related to indigenous community, and continuing profitability and therefore developing a sustainable living.